Bromodomain and extra-terminal motif inhibitors: a review of preclinical and clinical advances in cancer therapy. (29th January 2019) - Alqahtani, Ali; Choucair, Khalil; Ashraf, Mushtaq; Hammouda, Danae M; Alloghbi, Abduraham; Khan, Talal; Senzer, Neil; Nemunaitis, John
Histone lysine acetylation is critical in regulating transcription. Dysregulation of this process results in aberrant gene expression in various diseases, including cancer. The bromodomain, present in several proteins, recognizes promotor lysine acetylation and recruits other transcription factors. The bromodomain extra-terminal (BET) family of proteins consists of four conserved mammalian members that regulate transcription of oncogenes such as MYC and the NUT fusion oncoprotein. Targeting the acetyl-lysine-binding property of BET proteins is a potential therapeutic approach of cancer. Consequently, following the demonstration that thienotriazolodiazepine small molecules effectively inhibit BET, clinical trials were initiated. We thus discuss the mechanisms of action of various BET inhibitors and the prospects for their clinical use as cancer therapeutics. Lay abstract: Addition of acetyl groups to histone proteins that are present in DNA is critical for proper copying of genetic information into producing proteins. This process is dysregulated in various diseases including cancer, resulting in continuous production of oncogenes – genes responsible for promoting cancer – such as NUT and MYC . Bromodomain extra-terminal (BET) proteins mediate acetyl addition, and as a result, transcription. BET inhibitors are small molecules that block the action of BET proteins and the transcription of oncogenes. In this review, we discuss the different available BET inhibitors, the way they act, and their potential use in clinical settings for cancer treatment.